2008
DOI: 10.1097/acm.0b013e318183c5a7
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and Interpretive Skills of Medical Students: Experiences and Attitudes of Fourth-Year Students

Abstract: A majority of fourth-year medical students still have never performed important procedures, and a substantial minority have not performed basic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 4 publications
3
42
0
Order By: Relevance
“…This is often the first time students are required to take their knowledge out of the classroom and apply it to patients in the hospital. In addition to the clinical knowledge that must be developed, understanding of and continued refinement of technique must be practiced across a wide range of procedures [1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…This is often the first time students are required to take their knowledge out of the classroom and apply it to patients in the hospital. In addition to the clinical knowledge that must be developed, understanding of and continued refinement of technique must be practiced across a wide range of procedures [1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…6 Studies have shown that fourth-year students are aware of specific deficits, like the musculoskeletal examination and procedural skills, and of broader deficits which include medical decision making, differential diagnosis, and fund of knowledge. [7][8][9] Students can use the fourth year to address these deficits. Alternatively, students may prepare for internship, audition for residencies, conduct research, create unique experiences, or sample courses that will be henceforth unavailable.…”
mentioning
confidence: 99%
“…In order to meet this aspiration, curricula of many medical schools state the clinical practical skills so that students must demonstrate competence by the time they graduate, yet many graduate without learning these mostly common and some potentially lifesaving skills to the detriment of the quality of care for patients (Moercke & Eika, 2002;Colberly & Godenhar, 2006;Elango et al, 2007;Wu et al, 2008;Promes et al, 2009;Institute for Health Care Improvement, 2010).…”
Section: Introductionmentioning
confidence: 99%